Eksplorasi Pemanfaatan Aplikasi LinkedIn sebagai Strategi untuk Menarik Minat Generasi Z ke Dunia Kerja - Febriyanti, Salma Ayu; Setiasih, Esti Nur; Rhama, Bhayu; Selvia, Fitriana (Jurnal Politik dan Pemerintahan Daerah, 2025)
This study aims to explore the use of the LinkedIn platform as an innovative strategy in attracting Generation Z to enter the workforce. The focus of the study is directed to how LinkedIn acts as a medium for forming an individual's professional image and as a strategic tool for organizations in strengthening employer branding. The research method used is descriptive qualitative approach through the study of literature (library research). Data were collected from various scientific sources, such as national and international journals indexed by SINTA and Google Scholar, in the period 2015-2025. The analysis process is carried out by content analysis which includes stages of data reduction, theme categorization, and interpretation of findings to build a comprehensive conceptual understanding. The results show that LinkedIn plays an important role in two main dimensions. First, for Generation Z individuals, LinkedIn is an effective medium for developing personal branding, increasing competence, and expanding professional networking. Second, for organizations, LinkedIn serves as a means of employer branding that allows companies to display values, work culture, as well as a positive reputation to attract potential young Labor candidates. The integration between these two roles results in a mutually beneficial relationship between the individual and the organization. This research confirms that utilizing LinkedIn can be a two-way strategy that strengthens Generation Z's career readiness while supporting an organization's reputation in the digital age.